Glacial retreat converts exposed landscapes from net carbon sinks to sources - A. J. Pain; J. B. Martin; E. E. Martin; J. T. Salinas-Reyes; C. Bennett (Communications Earth & Environment)
Abstract Retreat of continental ice sheets exposes comminuted sediment in disequilibrium with non-glacial conditions. Weathering of this sediment may create climate feedbacks by altering exchange of greenhouse gases between atmosphere and landscapes. Here we show in a partially deglaciated watershed in southwest Greenland that glacial meltwater contains low concentrations of reactive dissolved organic carbon that enhances weathering of freshly comminuted sediment causing net sequestration of carbon dioxide. In contrast, soil water reactions enhance methanogenesis and carbon dioxide production and create greenhouse gas sources as organic carbon is remineralized. We suggest that a change from greenhouse gas sinks in glacial meltwater to greenhouse gas sources in soil water creates a switch from a negative to positive warming feedback during glacial-interglacial transitions, but a negative warming feedback may return with future anthropogenic warming, glacial retreat, and increased meltwater production. We anticipate changing weathering reactions following exposure also alter nutrient and radiogenic isotope exports.